A rapid and reliable PCR method for detecting clonal T cell populations. Issue 2 (April 1995) - Lynas, C; Howe, D; Copplestone, J A; Johnson, S A N; Phillips, M J
Abstract : Aims —To establish a reverse transcription polymerase chain reaction (RT-PCR) for the detection of clonal T cell populations, and to evaluate the sensitivity and reliability of the technique. Methods —After reverse transcription of the target RNA with a consensus T cell receptor (TCR) β constant (C) region primer, consensus C, variable (V), diversity (D) and joining (J) region primers were used to amplify across various portions of the TCRβ V-D-J-C junction. Results —In normal T cells the polyclonal rearrangements produce a ladder of PCR bands representing the different sized junction fragments. The presence of a T cell clone leads to over-representation of one junction fragment, hence a disproportionately brighter band in the PCR ladder. In a series of 16 patients the RT-PCR detected nine of nine shown to have a clonal TCRβ rearrangement by Southern blotting and for six of seven patients, it confirmed the presence of a clone indicated by histology or immunophenotyping with FACS analysis, but which was undetectable (five patients) or not investigated (two patients) by Southern blotting. Investigations mixing RNA from normal lymphocytes and the Jurkat TCR-Vβ8 T cell line suggested that the method was more sensitive than Southern blotting. Conclusions —All PCR methods are faster and easier than Southern blotting, but RT-PCR also improves detection of clonal T cell populations, is reliable and produces results that are easy to interpret.